Trzy skandale, trzy raporty. Redakcje i ombudsmani prasowi w sytuacjach kryzysowych na przykładach „The Washington Post”, „The New York Times” i „Los Angeles Times” - Adamczyk, Wojciech (Przegląd Politologiczny, 2018)
The paper deals with the issue of the supervision of the media that frequently exceed the standards observed by journalistic circles and their social environments. The direct victims of breaches of deontological principles in the profession and work of journalists primarily involve the recipients, journalistic circles and the reputation of a given medium. There are also indirect consequences, such as a loss of confidence that translates into lower sales or reduced advertising. In the cases that are commonly termed media scandals a crisis situation emerges. The analysis of the problem and the recovery of a tarnished reputation and lost confidence of recipients are usually performed by teams of experienced journalists, appointed ad hoc by edi-torial boards or by press ombudsmen working in the media, which is much less frequent. This paper discusses both scenarios. Three famous scandals have been selected from among many examples. One involves the 1980 case of the journalist Janet Cooke from The Washington Post whose Pulitzer Prize was withdrawn after she admitted that her award-winning story was a fabrication. Another case is the equally high-profile case of The Los Angeles Times from 1999, which marked a conflict of interest, following the publication of a special issue devoted to the sports arena that was being erected in the city at that time. The third scandal occurred in The New York Times in 2003, and concerned mass plagiarism and fabrication of press materi- als by that daily’s reporter, Jason Blair. The attempts to regain reader trust involved, among other things, the publication of reports drawn up by specially appointed teams of press ombudsmen.